Concentrações de cobre ambientalmente relevantes afetam a fisiologia em Chlorolobion Braunii - Silva, Douglas Henrique Baracho da (2018)
Copper plays vital role in microalgae metabolism, but what we know about it is largely based in studies conducted with high copper concentrations, much less is known when environmentally relevant copper concentrations in microalgae physiology comes into question. Here, we evaluated the physiology of Chlorolobion braunii exposed to free copper ions concentrations between 5.7x10-9 to 5.0x10-6 mol L-1, thus including environmentally relevant values. Population growth and photosynthetic parameters were determined in 96 h controlled laboratory experiments. Exponentially growing cells (48 h cultures) were analyzed for effective quantum yield and rapid light curves (RLC), as well as total lipids, proteins and carbohydrates, chlorophyll a and carotenoids concentrations. Results showed that growth rates and population density decreased gradually as copper increased in cultures, with chlorophyll a concentration been affected less intensively than the growth parameters. Up to 4.0x10-6 mol L-1 free copper no effect was obtained for maximum and effective quantum yields, and photochemical quenching (qP). However, at 5.0x10-6 mol L-1 they were drastically reduced and non-photochemical quenching (NPQ) increased. Rapid light curves and their parameters (Ek, α and ETRmax) were inversely correlated with free copper concentrations. The yield of biomolecules increased under environmentally relevant copper concentrations, situation where the absolute values were not affected. Two important applications can be delineated from the present research, one related to ecology and the other one to biotechnology. Because copper concentration in the environment is gradually increasing due to anthropic activities, investigations that use environmentally relevant values are of interest to both ecology and microalgae physiology, and closer to reality than acute toxicological investigations.